Mass spectroscopy reveals compositional differences in copepodamides from limnic and marine copepods - Sina Arnoldt; Milad Pourdanandeh; Ingvar Spikkeland; Mats X. Andersson; Erik Selander (Scientific Reports)
Abstract Marine copepods, the most abundant animals in the global ocean, imprint their surrounding waters with chemical cues, called copepodamides. Copepodamides induce defensive traits such as toxin production, bioluminescence, and colony size plasticity in a variety of marine phytoplankton. The role of copepodamides in freshwater ecosystems is, however, unknown. Here we report the consistent presence of copepodamides in copepods from six Swedish freshwater lakes. Copepodamide concentrations in freshwater copepods are similar to those of marine copepods, around 0.1 ppt of dry mass in millimetre sized individuals. The composition substantially overlaps with marine copepodamides but is also distinctly different. Marine copepods commonly contain both subgroups of copepodamides, the copepodamides (CA) and the dihydro-copepodamides (dhCA), whereas freshwater copepods are dominated by the dhCAs. Taxonomic groups had consistent copepodamide profiles across sampling sites and timepoints, supporting the presence of species-specific copepodamide signatures. We describe 10 new copepodamide structures, four of which were found exclusively in freshwater copepods. The presence of copepodamides in limnic copepods also warrants studies into their potential function as predator alarm cues in freshwater systems.